Energy Transfers by Convection - Benallou, Abdelhanine (Energy series (ISTE Ltd.). Energy engineering set, 2019)
Whether in a solar thermal power plant or at the heart of a nuclear reactor, convection is an important mode of energy transfer. This mode is unique; it obeys specific rules and correlations that constitute one of the bases of equipment-sizing equations. In addition to standard aspects of convention, this book examines transfers at very high temperatures where, in order to ensure the efficient transfer of energy for industrial applications, it is becoming necessary to use particular heat carriers, such as molten salts, liquid metals or nanofluids. With modern technologies, these situations are becoming more frequent, requiring appropriate consideration in design calculations. Energy Transfers by Convection also studies the sizing of electronic heat sinks used to ensure the dissipation of heat and thus the optimal operation of circuit boards used in telecommunications, audio equipment, avionics and computers.